2016
DOI: 10.1371/journal.pone.0160811
|View full text |Cite
|
Sign up to set email alerts
|

A Protocolised Once a Day Modified Early Warning Score (MEWS) Measurement Is an Appropriate Screening Tool for Major Adverse Events in a General Hospital Population

Abstract: BackgroundThe Modified Early Warning Score (MEWS) was developed to timely recognise clinically deteriorating hospitalised patients. However, the ability of the MEWS in predicting serious adverse events (SAEs) in a general hospital population has not been examined prospectively. The aims were to (1) analyse protocol adherence to a MEWS protocol in a real-life setting and (2) to determine the predictive value of protocolised daily MEWS measurement on SAEs: death, cardiac arrests, ICU-admissions and readmissions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
46
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 24 publications
2
46
0
8
Order By: Relevance
“…Such finding is common amongst Italian Internal Medicine wards, where about 20% of Internal Medicine hospitalised patients needs more intensive care settings and treatments . We reported a total in‐hospital mortality of 6.2%, which is similar to mortality rate reported in a recent study aimed at determining the predictive value of the protocolised daily MEWS measurement on serious adverse events …”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Such finding is common amongst Italian Internal Medicine wards, where about 20% of Internal Medicine hospitalised patients needs more intensive care settings and treatments . We reported a total in‐hospital mortality of 6.2%, which is similar to mortality rate reported in a recent study aimed at determining the predictive value of the protocolised daily MEWS measurement on serious adverse events …”
Section: Discussionsupporting
confidence: 85%
“…Recently, the ability of the MEWS in predicting serious adverse events in a general hospital population has been examined prospectively. The study indicated the reliability of this score as screening tool …”
Section: Discussionmentioning
confidence: 83%
“…Patients of this study with increased MEWS values prior to unplanned ICU admissions showed increased ICU mortality rate (33.3%), compared with the general mortality rate for the whole ICU (19.7%). This was probably explained by the worse and prolonged physiological derangement of these patients (Subbe et al, ; van Galen, Dijkstra, Ludikhuize, Kramer, & Nanayakkara, ).…”
Section: Discussionmentioning
confidence: 99%
“…This policy can result in earlier admission to the ICU and reduction of preventable deaths (Cardoso et al, ). Based on the proven prognostic value of the MEWS, researchers have suggested the following cut‐off points as alarms for immediate action: scores ≥ 3 to score ≥ 5, with the higher scoring been associated with significantly more adverse events and increased risk of death (increased specificity) (Kim et al, ; Subbe et al, ; van Galen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In-hospital emergency systems using more sensitive criteria, including the National Early Warning System (NEWS) and the Modified Early Warning System (MEWS), which use scoring and alert systems based on a set of criteria, including temperature and oxygen saturation, in addition to urinary output, have been reported in the literature. (26,27) …”
Section: Discussionmentioning
confidence: 99%